P, Peningkatan PENINGKATAN LITERASI DIGITAL ORANG TUA DAN GURU MELALUI PELATIHAN APLIKASI PENCEGAHAN DINI KEKERASAN SEKSUAL PADA ANAK - Agus Wantoro; Nur Aminudin; Nuafal Sinatria (Dharma: Jurnal Pengabdian Masyarakat, 2026)
Sexual violence against children is a serious problem that requires early prevention efforts through the active involvement of parents and teachers. The development of digital technology presents opportunities to utilize educational applications as a medium to support the prevention of sexual violence against children. However, low digital literacy becomes an obstacle in optimizing the use of these applications. This community service activity aims to improve the digital literacy of parents and teachers through training in the use of applications for the early prevention of sexual violence against children. The methods used include participatory and educational approaches through the delivery of materials, demonstrations, hands-on practice, and interactive discussions. The results of the activity showed an increase in participants' understanding of the importance of early prevention of sexual violence as well as an improvement in skills in utilizing digital applications as a medium for education and child protection. This training contributes to strengthening the role of parents and teachers in creating a safe and child-friendly environment. This activity is expected to serve as a model of sustainable technology-based service in supporting child protection efforts